A multi-center interventional study to assess pharmacokinetics, effectiveness, and tolerability of prolonged-release tacrolimus after pediatric kidney transplantation: study protocol for a prospective, open-label, randomized, two-phase, two-sequence, single dose, crossover, phase III b trial - Karaterzi, Sinem; Tönshoff, Burkhard; Ahlenstiel-Grunow, Thurid; Baghai, Maral; Beck, Bodo; Büscher, Anja; Eifler, Lisa; Giese, Thomas; Lezius, Susanne; Müller, Carsten; Oh, Jun; Zapf, Antonia; et al. (Frontiers in Nephrology, 2024)
Background Tacrolimus, a calcineurin inhibitor (CNI), is currently the first-line immunosuppressive agent in kidney transplantation. The therapeutic index of tacrolimus is narrow due to due to the substantial impact of minor variations in drug concentration or exposure on clinical outcomes (i.e., nephrotoxicity), and it has a highly variable intra- and inter-individual bioavailability. Non-adherence to immunosuppressants is associated with rejection after kidney transplantation, which is the main cause of long-term graft loss. Once-daily formulations have been shown to significantly improve adherence compared to twice-daily dosing. Envarsus®, the once-daily prolonged-release formulation of tacrolimus, offers the same therapeutic efficacy as the conventional twice-daily immediate-release tacrolimus formulation (Prograf®) with improved bioavailability, a more consistent pharmacokinetic profile, and a reduced peak to trough, which may reduce CNI-related toxicity. Envarsus® has been approved as an immunosuppressive therapy in adults following kidney or liver transplantation but has not yet been approved in children. The objective of this study is to evaluate the pharmacokinetic profile, efficacy, and tolerability of Envarsus® in children and adolescents aged ≥ 8 and ≤ 18 years to assess its potential role as an additional option for immunosuppressive therapy in children after kidney transplantation. Methods/design The study is designed as a randomized, prospective crossover trial. Each patient undergoes two treatment sequences: sequence 1 includes 4 weeks of Envarsus® and sequence 2 includes 4 weeks of Prograf®. Patients are randomized to either group A (sequence 1, followed by sequence 2) or group B (sequence 2, followed by sequence 1). The primary objective is to assess equivalency between total exposure (of tacrolimus area under the curve concentration (AUC0-24)), immediate-release tacrolimus (Prograf®) therapy, and prolonged-release tacrolimus (Envarsus®) using a daily dose conversion factor of 0.7 for prolonged- versus immediate-release tacrolimus. Secondary objectives are the assessment of pharmacodynamics, pharmacogenetics, adherence, gut microbiome analyses, adverse events (including tacrolimus toxicity and biopsy-proven rejections), biopsy-proven rejections, difference in estimated glomerular filtration rate (eGFR), and occurrence of donor-specific antibodies (DSAs). Discussion This study will test the hypothesis that once-daily prolonged-release tacrolimus (Envarsus®) is bioequivalent to twice-daily intermediate-release tacrolimus after pediatric kidney transplantation and may reduce toxicity and facilitate medication adherence. This novel concept may optimize immunosuppressive therapy for more stable graft function and increased graft survival by avoiding T-cell mediated and/or antibody-mediated rejection due to improved adherence. In addition, the study will provide data on the pharmacodynamics and pharmacogenetics of prolonged-release tacrolimus in children and adolescents. Clinical Trial Registration EUDRA-CT 2019-003710-13 and ClinicalTrial.gov, identifier NCT06057545.